2022
DOI: 10.1038/s41598-022-07009-6
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod-driven rhythms reveal multi-decadal stability of phytoplankton communities in a highly fluctuating coastal environment

Abstract: Phytoplankton play a pivotal role in global biogeochemical and trophic processes and provide essential ecosystem services. However, there is still no broad consensus on how and to what extent their community composition responds to environmental variability. Here, high-frequency oceanographic and biological data collected over more than 25 years in a coastal Mediterranean site are used to shed light on the temporal patterns of phytoplankton species and assemblages in their environmental context. Because of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 83 publications
7
18
0
Order By: Relevance
“…To correct the attribution of ambiguous ancillary haplotypes, we assume that all haplotypes belonging to the same taxon, that is, to the same population of freely interbreeding individuals, share a comparable distribution of reads over the sample dates. This expectation is supported by the marked seasonality of the Pseudo-nitzschia species observed in this study, as already found in previous studies based on environmental clone libraries (McDonald et al, 2007;Ruggiero et al, 2015) and on the analysis of the whole phytoplankton community (Longobardi et al, 2022) in the GoN.…”
Section: Species Delimitationsupporting
confidence: 92%
“…To correct the attribution of ambiguous ancillary haplotypes, we assume that all haplotypes belonging to the same taxon, that is, to the same population of freely interbreeding individuals, share a comparable distribution of reads over the sample dates. This expectation is supported by the marked seasonality of the Pseudo-nitzschia species observed in this study, as already found in previous studies based on environmental clone libraries (McDonald et al, 2007;Ruggiero et al, 2015) and on the analysis of the whole phytoplankton community (Longobardi et al, 2022) in the GoN.…”
Section: Species Delimitationsupporting
confidence: 92%
“…Yet, phenology, that is, the seasonal time window of species' occurrences, has rarely been considered a stable, endogenous character in phytoplankton, whereby the alternation of different species over the seasons is postulated to be strictly driven by changes in environmental conditions. Nevertheless, annually recurrent patterns are seen in long‐term analysis of nano‐ and microphytoplankton species of the Gulf of Naples, where photoperiod is the most important explanatory variable driving community turnover (Longobardi et al, 2022 ; Ribera d'Alcalà et al, 2004 ). Recent massive eDNA sequencing from other areas has also revealed recurrent occurrence of picoplanktonic taxa against marked environmental variability (Giner et al, 2019 ; Lambert et al, 2019 ), which can be explained based on endogenous rhythms and stability of phenological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, annually recurrent patterns are seen in long-term analysis of nano-and microphytoplankton species of the Gulf of Naples, where photoperiod is the most important explanatory variable driving community turnover (Longobardi et al, 2022;Ribera d'Alcalà et al, 2004) The mechanisms underlying allochronic speciation, and speciation in general, are not easy to clarify (Orsini et al, 2013), as both neutral and selective processes could be involved. Time and environmental variables covary, making it difficult to discern their respective contribution to the patterns observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the observed dynamics in read relative abundance results from many different processes affecting either cell growth or cell losses via diverse mechanisms (for example, sedimentation, grazing, programmed cell death, internal clock, or infection by parasites). The synchronic variations in read contribution to total counts in such different and geographically distant sites could indicate that internal controls of growth rate and sexual reproduction, rather that external environmental parameters are at work (Cianelli et al, 2017; D’Alelio et al, 2010; Jewson et al, 2016; Longobardi et al 2022). The 4 other species, identified as core and abundant in the 2 sites, may be more adapted to respond to natural environmental variability, and take advantage, for example, of pulses of nutrients.…”
Section: Discussionmentioning
confidence: 99%